Cucumeropsis mannii seed oil shields against cyclophosphamide-induced hepatorenal toxicity by modulating redox imbalance and iNOS/IL-β1 signalling in rats - Amaka Cecilia Agbara; Ejike Daniel Eze; Christian Emeka Offor; Adam Moyosore Afodun; Ezebuilo Ugbala Ekpono; Peter Chinedu Agu; Chinyere Aloke; Nkeiru Nwaamaka Ezeani; Emmanuel Orire Ikuomola; Ekom Monday Etukudo; Ilemobayo Victor Fasogbon; Angela Mumbua Musyoka; et al. (Heliyon)
This study aimed to determine whether C. mannii seed oil (CMSO) could shield rats from cyclophosphamide-induced hepatorenal toxicity. The focus was on its antioxidant and anti-inflammatory properties. We randomly assigned thirty-six (36) male Wistar rats into six groups of six rats each. Groups A and B served as normal and negative controls, respectively. Group C, the standard control, was administered 300 mg/kg body weight (bw) of Omega 3 oil for 27 days, followed by 100 mg/kg bw of cyclophosphamide on day 28. Group D, E, and F received 5, 2.5, and 1.5 ml/kg b.w. of CMSO for 27 days, then 100 ml/kg b.w. of cyclophosphamide on day 28. We measured the body weights of the experimental rats every week. Rats of all groups were sacrificed on day 30 and collected blood for biochemical analysis using standard methods. The phytochemical constituents were determined by the spectrophotometric method. The phytochemical study of CMSO indicated the relative composition of constituents(mg/100g) as phenols (30 %), tannins (20 %), flavonoids (18 %), terpenoids (15 %), glycosides (10 %), alkaloids (5 %), and HCN (2 %) in Cucumeropsis mannii seed oil. When cyclophosphamide was given to Wistar albino rats, it greatly decreased the activities of catalase (CAT) and superoxide dismutase (SOD), but it increased the activities of iNOS and the levels of MDA and IL-1β. Cyclophosphamide increased ALT (52.3 U/L), AST (48.7 U/L), ALP (46.5 U/L), total bilirubin (1.4 mg/dL), conjugated bilirubin (0.8 mg/dL), creatinine (0.8 mg/dL), urea (45.6 mg/dL), and BUN (15.7 mg/dL), with a reduction in the albumin (4.8 g/dL) level. Cyclophosphamide administration also caused hepatocellular necrosis, inflammatory leukocyte infiltration, tubular necrosis, and proteinaceous deposits in Bowman's space in the kidney. However, combining CMSO and Omega 3 oils significantly restored the altered histology architecture, antioxidant, inflammatory markers, and liver and kidney function parameters to levels comparable to the normal group, thereby reducing the harmful effects of cyclophosphamide. This effect did not depend on the dose. These results suggest that CMSO, being an antioxidant and an anti-inflammatory, could potentially aid in preventing and treating hepatorenal toxicity resulting from cyclophosphamide.